2023
DOI: 10.3390/ijms24043296
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Structural Relationship between Thyroid Hormone-Signaling Disruption and Polybrominated Diphenyl Ethers: Potential Implications for Male Infertility

Abstract: Polybrominated diphenyl ethers (PBDEs) are a common class of anthropogenic organobromine chemicals with fire-retardant properties and are extensively used in consumer products, such as electrical and electronic equipment, furniture, textiles, and foams. Due to their extensive use, PBDEs have wide eco-chemical dissemination and tend to bioaccumulate in wildlife and humans with many potential adverse health effects in humans, such as neurodevelopmental deficits, cancer, thyroid hormone disruption, dysfunction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Another potential disruptive mechanism is competitive binding of PBDEs with TRs, as demonstrated in cell and animal experiments. In vitro cell studies have shown that PBDEs have an affinity similar to FT3 for binding with TRs (TRα and TRβ), thereby hindering FT3 activation in tissues. Electrostatic interaction and hydrophobic interactions significantly contribute to the interference with TH-protein binding . Molecular dynamics simulations estimates on 18 OH-PBDEs reveals that the presence of more Br atom in OH-PBDEs results in stronger binding potential with THRβ-LBD .…”
Section: Discussionmentioning
confidence: 99%
“…Another potential disruptive mechanism is competitive binding of PBDEs with TRs, as demonstrated in cell and animal experiments. In vitro cell studies have shown that PBDEs have an affinity similar to FT3 for binding with TRs (TRα and TRβ), thereby hindering FT3 activation in tissues. Electrostatic interaction and hydrophobic interactions significantly contribute to the interference with TH-protein binding . Molecular dynamics simulations estimates on 18 OH-PBDEs reveals that the presence of more Br atom in OH-PBDEs results in stronger binding potential with THRβ-LBD .…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al found that BTBPE levels reduced protein levels of PAX8, TTF1, and TTF2, inhibiting thyroglobulin and NIS [ 25 ]. More recent studies have begun analyzing the molecular relationships between specific flame retardants and thyroid hormones, including analysis of binding energies [ 13 ]. Sheikh et al analyzed the structural binding of PBDEs against the ligand binding pocket of thyroid receptor alpha and identified the specific amino acid residues and quantified the interactions in the binding pocket [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have begun analyzing the molecular relationships between specific flame retardants and thyroid hormones, including analysis of binding energies [ 13 ]. Sheikh et al analyzed the structural binding of PBDEs against the ligand binding pocket of thyroid receptor alpha and identified the specific amino acid residues and quantified the interactions in the binding pocket [ 13 ]. Within human hepatic tissue, PBDEs are converted into their more active metabolite, OH-PBDEs, a chemical with even greater structural similarity to thyroid hormones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation